STUDI PENGARUH HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK FMCG (FAST MOVING CONSUMER GOODS) DI RANTAU KALIMANTAN SELATAN - Alvina Wigati; Febsri Susanti (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to analyze the influence of price and promotion on purchasing decisions for FMCG products in Rantau, South Kalimantan. This research uses a quantitative approach with a survey method, involving 100 respondents who are consumers of FMCG products in the area. Data was obtained through a questionnaire and analyzed using linear regression to test the relationship between price and promotion variables and purchasing decisions. The research results show that price has a significant influence on purchasing decisions, with a coefficient of 0.45, which shows that competitive prices can increase consumers' tendency to buy FMCG products. Apart from that, promotions were also proven to have a significant effect with a coefficient of 0.52, where types of promotions such as discounts and loyalty programs were proven to be effective. The combination of price and promotion shows a greater influence on purchasing decisions, with a coefficient of determination (R²) of 0.67. This research provides insight for FMCG companies in designing effective marketing strategies, by considering the influence of price and promotion simultaneously in influencing consumer behavior.